Imaging mass cytometry reveals generalised deficiency in OXPHOS complexes in Parkinson’s disease - Chun Chen; David McDonald; Alasdair Blain; Ashwin Sachdeva; Laura Bone; Anna L. M. Smith; Charlotte Warren; Sarah J. Pickett; Gavin Hudson; Andrew Filby; Amy E. Vincent; Doug M. Turnbull; et al. (npj Parkinson's Disease, 2021)
Abstract Here we report the application of a mass spectrometry-based technology, imaging mass cytometry, to perform in-depth proteomic profiling of mitochondrial complexes in single neurons, using metal-conjugated antibodies to label post-mortem human midbrain sections. Mitochondrial dysfunction, particularly deficiency in complex I has previously been associated with the degeneration of dopaminergic neurons in Parkinson’s disease. To further our understanding of the nature of this dysfunction, and to identify Parkinson’s disease specific changes, we validated a panel of antibodies targeting subunits of all five mitochondrial oxidative phosphorylation complexes in dopaminergic neurons from Parkinson’s disease, mitochondrial disease, and control cases. Detailed analysis of the expression profile of these proteins, highlighted heterogeneity between individuals. There is a widespread decrease in expression of all complexes in Parkinson’s neurons, although more severe in mitochondrial disease neurons, however, the combination of affected complexes varies between the two groups. We also provide evidence of a potential neuronal response to mitochondrial dysfunction through a compensatory increase in mitochondrial mass. This study highlights the use of imaging mass cytometry in the assessment and analysis of expression of oxidative phosphorylation proteins, revealing the complexity of deficiencies of these proteins within individual neurons which may contribute to and drive neurodegeneration in Parkinson’s disease.